Novel environmental and sustainable approach for concurrent assay of antineoplastics in VMP regimen with a comprehensive Pharmacokinetic study - Marco M. Z. Sharkawi; Noha H. Amin; Norhan R. Mohamed; Shimaa S. Zaki; Loah R. Hemeda (Scientific Reports)
Abstract Multiple myeloma (MM) is a blood cancer that, unfortunately, has a high morbidity and mortality rate. The VMP regimen, which includes bortezomib (BOR), melphalan (MEL), and prednisolone (PRD), is a safe and effective salvage regimen for refractory or relapsed MM. Up to now, there is no established analytical method to determine the VMP regimen, nor has any study investigated the kinetic interactions among its components, thereby highlighting the need for further clinical investigation. In light of this, an environmentally friendly, fast, sensitive, and precise LC-MS/MS method was established to determine bortezomib, melphalan, prednisolone, and sildenafil (an internal standard) simultaneously as part of the in vivo pharmacokinetics research carried out on rats. The established LC-MS/MS method was applied using a mobile phase composed of a mixture of methanol: 0.1% aqueous solution of formic acid and a ZORBAX Eclipse Plus C18 column (4.6 mm × 150 mm, 5 μm) as a stationary phase. The cited drugs were ionized through positive ionization and detected using multi-reaction monitoring (MRM) mode with the following precursor→product transitions: m/z 367.3→226.3 for BOR, m/z 305.0→168.2 for MEL, m/z 545.0→147.5 for PRD, and m/z 475.3→283.4 for SIL. Following FDA guidelines, the developed method was validated and showed acceptable ranges. Subsequently, it was employed in an in vivo investigation using rats, where the quantitative assessment of each drug was performed following both single and combined treatment. This allowed for the investigation of potential drug-drug interactions and the calculation of all pharmacokinetic parameters to monitor the therapeutic effects of those medications. To ensure the safety and environmental friendliness of the developed method, four assessment tools were applied: the assessment of green profile (AGP), blue applicability grade index (BAGI), analytical greenness metric for sample preparation (AGREEprep), and green analytical procedure index (GAPI).